2014
DOI: 10.2754/avb201483040287
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella serovar spectrum associated with reptiles in Poland

Abstract: This study aimed to evaluate the incidence of Salmonella isolates from a wide variety of reptiles in Poland. A total of 374 faecal samples from chelonians, lizards and snakes were collected between 2009 and 2012. The nested, two-step PCR and multiplex PCR were performed to access the incidence and to characterize Salmonella isolates. Salmonella strains were found in 122 of 374 samples (32.6%). Among the different reptilian species, Salmonella strains were found in 58 samples from lizards (38.9%), 31 samples fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
(22 reference statements)
1
12
1
Order By: Relevance
“…prevalence was observed in lizards (25.6%), followed by snakes (17.6%) and chelonians (8%; Table 1). The prevalence rates in these groups of reptiles are consistent with the findings of other authors (De Sa and Solari 2001;Piasecki et al 2014;Lukac et al 2015). The increased diagnostic yield could be affected by the number of lizards as they constituted the largest group in this study (86/153), and many of them were examined repeatedly.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…prevalence was observed in lizards (25.6%), followed by snakes (17.6%) and chelonians (8%; Table 1). The prevalence rates in these groups of reptiles are consistent with the findings of other authors (De Sa and Solari 2001;Piasecki et al 2014;Lukac et al 2015). The increased diagnostic yield could be affected by the number of lizards as they constituted the largest group in this study (86/153), and many of them were examined repeatedly.…”
Section: Discussionsupporting
confidence: 80%
“…of about 19% in the studied reptiles. Available literature sources have reported varying levels of prevalence, namely, 54.1% in Germany and Austria (Geue and Loschner 2002), 32.6% in Poland (Piasecki et al 2014), 49% in Sweden (Wikstrom et al 2014), 13% in Croatia (Lukac et al 2015), 30.9% in Taiwan (Chen et al 2010) and 13.6% in Italy (Bertelloni et al 2016). Our results did not differ significantly from those obtained in other countries.…”
Section: Discussioncontrasting
confidence: 31%
See 1 more Smart Citation
“…enterica that was detected with 35.1% frequency in Caspian pond turtles, was found by other investigators to be predominant serotype, too. 15,28,29 As difference in the prevalence of Salmonella colonization can be seen in animals across different geographical locations, serovars identified in the present study could not be reasonably compared with data from other countries. It seems that serotype dominancy depends on different factors such as the region and whole reservoir of Salmonella in each ecosystem.…”
Section: 24mentioning
confidence: 72%
“…28 Another survey conducted in 1999 in Poland which incorporated over 300 000 animals and food samples showed that the most common serovar of Salmonella was S. enteritidis. 29 Salmonella enterica subsp.…”
Section: 24mentioning
confidence: 99%